2010
DOI: 10.1111/j.1469-8137.2010.03538.x
|View full text |Cite
|
Sign up to set email alerts
|

Rice SIZ1, a SUMO E3 ligase, controls spikelet fertility through regulation of anther dehiscence

Abstract: Summary• Sumoylation, a post-translational modification, has important functions in both animals and plants. However, the biological function of the SUMO E3 ligase, SIZ1, in rice (Oryza sativa) is still under investigation.• In this study, we employed two different genetic approaches, the use of siz1 T-DNA mutant and SIZ1-RNAi transgenic plants, to characterize the function of rice SIZ1.• Genetic results revealed the co-segregation of single T-DNA insertional recessive mutation with the observed phenotypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 69 publications
0
54
0
2
Order By: Relevance
“…A similar suppression was seen in Arabidopsis, indicating that this stress memory might be universal in terrestrial plants (Kurepa et al, 2003). The protective role of SUMO conjugation during stress also is supported by the stress-sensitive phenotypes associated with SUMO pathway loss-of-function mutants in Arabidopsis, rice, and yeast (Tanaka et al, 1999;Miura et al, 2007;Conti et al, 2008;Golebiowski et al, 2009;Chaikam and Karlson, 2010;Thangasamy et al, 2011). Less clear is how SUMO protects organisms from suboptimal growth conditions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A similar suppression was seen in Arabidopsis, indicating that this stress memory might be universal in terrestrial plants (Kurepa et al, 2003). The protective role of SUMO conjugation during stress also is supported by the stress-sensitive phenotypes associated with SUMO pathway loss-of-function mutants in Arabidopsis, rice, and yeast (Tanaka et al, 1999;Miura et al, 2007;Conti et al, 2008;Golebiowski et al, 2009;Chaikam and Karlson, 2010;Thangasamy et al, 2011). Less clear is how SUMO protects organisms from suboptimal growth conditions.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies with rice (Oryza sativa) showed that SUMOylation is active in growing tissues and, like that in Arabidopsis, is strongly up-regulated upon exposure to heat, cold, high salt, and abscisic acid (Chaikam and Karlson, 2010;Park et al, 2010). Rice siz1 alleles that attenuate SUMOylation have a smaller stature with a reduced root system, greater tillering, and reduced fecundity (Thangasamy et al, 2011) and accumulate higher levels of nitrogen and phosphorous, possibly due to the altered expression of genes involved in nutrient uptake (Wang et al, 2015). Conversely, OTS1 overexpression rendered rice resistant to high salt, whereas RNA interference-mediated silencing enhanced salt sensitivity (Srivastava et al, 2016).…”
mentioning
confidence: 99%
“…The OsSIZ1 and AtSIZ1 proteins share 51% identity at the amino acid level (Park et al 2010). The SUMO E3 ligase is known to regulate various aspects of plant growth and development such as ABA signaling (Miura et al 2009), innate immunity through salicylic acid signaling (Miura and Hasegawa 2010), nitrogen assimilation (Park et al 2011), spikelet fertility in rice (Thangasamy et al 2011) and flowering (Jin et al 2008). Besides its roles in regulating plant growth and development, Arabidopsis SIZ1 was shown to play roles in stress tolerance against various environmental stresses such as low temperature stress via sumoylation and stabilization of the ICE1 transcription factor (Miura et al 2007b), heat stress (Kurepa et al 2003, Yoo et al 2006, Saracco et al 2007), water deficit stress (Catala et al 2007), phosphate starvation stress (Miura et al 2005) and metal stress such as copper stress (Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…DEFECTIVE IN ANTHER DEHISCENCE1 (DAD1) gene encodes phospholipase enzyme required for jasmonic acid biosynthesis and regulates anther dehiscence in Arabidopsis. Knock-down/Knock-out of SIZ1 , a SUMO E3 ligase gene, resulted in sterile rice plant due to lack of anther dehiscence24. Pollen Semi-Sterility1 (PSS1) encodes a kinesin-like protein that regulates both pollen development and anther dehiscence process in rice25.…”
mentioning
confidence: 99%